Objetos de prestigio en retratos de mujeres criollas. Audiencia de Quito, período borbónico tardío (Estudios) - Martínez Borrero, Juan (2020)
The article examines portraits, correspondence and personal belongings of María Josefa de Velasco and María Margarita Carrión in order to discover how creole women used jewels and dresses to shape their public and private image. By studying the tangible culture and ascertaining the price, variety, origin and circulation of these items, it addresses their social use and significance. The period of time under review extends from the inclusion of the Audiencia of Quito into the Viceroyalty of Nueva Granada to the establishment of the first autonomous junta, which was the last stage in which the items that were used reproduced colonial patterns of social conduct.